Magnesium Deficiency Causes a Reversible, Metabolic, Diastolic Cardiomyopathy - Man Liu; Hong Liu; Feng Feng; An Xie; Gyeoung‐Jin Kang; Yang Zhao; Cody R. Hou; Xiaoxu Zhou; Samuel C. Dudley (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Dietary Mg intake is associated with a decreased risk of developing heart failure, whereas low circulating Mg level is associated with increased cardiovascular mortality. We investigated whether Mg deficiency alone could cause cardiomyopathy. Methods and Results C57BL/6J mice were fed with a low Mg (low‐Mg, 15–30 mg/kg Mg) or a normal Mg (nl‐Mg, 600 mg/kg Mg) diet for 6 weeks. To test reversibility, half of the low‐Mg mice were fed then with nl‐Mg diet for another 6 weeks. Low‐Mg diet significantly decreased mouse serum Mg (0.38±0.03 versus 1.14±0.03 mmol/L for nl‐Mg; P<0.0001) with a reciprocal increase in serum Ca, K, and Na. Low‐Mg mice exhibited impaired cardiac relaxation (ratio between mitral peak early filling velocity E and longitudinal tissue velocity of the mitral anterior annulus e, 21.1±1.1 versus 15.4±0.4 for nl‐Mg; P=0.011). Cellular ATP was decreased significantly in low‐Mg hearts. The changes were accompanied by mitochondrial dysfunction with mitochondrial reactive oxygen species overproduction and membrane depolarization. cMyBPC (cardiac myosin‐binding protein C) was S‐glutathionylated in low‐Mg mouse hearts. All these changes were normalized with Mg repletion. In vivo (2‐(2,2,6,6‐tetramethylpiperidin‐1‐oxyl‐4‐ylamino)‐2‐oxoethyl)triphenylphosphonium chloride treatment during low‐Mg diet improved cardiac relaxation, increased ATP levels, and reduced S‐glutathionylated cMyBPC. Conclusions Mg deficiency caused a reversible diastolic cardiomyopathy associated with mitochondrial dysfunction and oxidative modification of cMyBPC. In deficiency states, Mg supplementation may represent a novel treatment for diastolic heart failure.